(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Aims and Objectives: to assess the spectrum of coronary and non-coronary artery anatomy and its various anomalies as depicted on CT angiography. Material and Method: A prospective observational study was conducted in department of Radiodiagnosis, KGMU, for one year duration. CT Angiography (CTA) was done in 64 SLICE MDCT SCANNER (PHILIPS BRILLIANCE, Netherland). Study included pediatric population (age 1 - 20 years) having complaints of acute chest pain and suspected coronary artery disease with or without equivocal findings in 2D ECHO. Patients with Allergy to iodinated contrast agents, Cardiac arrhythmias, Renal insufficiency (GFR <30 mL/min), history of asthma were excluded from the study. Results: Among total 20 enrolled patients 13 (65%) had coronary anomaly and 7 (35%) had extra-coronary anomaly. CT coronary angiography has 100% PPV for diagnosis of coronary and extra coronary anomalies. Conclusion: ECG-gated multidetector CTA is an essential imaging tool for evaluating the coronary arteries and extra coronary anomalies. Knowledge of the imaging anatomy of various cardiac anomalies is essential for accurate diagnosis and proper treatment. Pre procedure CTA will help in better planning and understanding the hemodynamic changes and better prognostication of disease.